Clostridium difficile carriage in healthy pregnant women in China. (February 2016) - Ye, Guang-yong; Li, Na; Chen, Yun-Bo; Lv, Tao; Shen, Ping; Gu, Si-Lan; Fang, Yun-hui; Li, Lan-Juan
Abstract: Infection with Clostridium difficile has been shown to have particularly poor outcomes for pregnant women, including an increased risk of death. The purpose of this study was to investigate the prevalence, genotypic distribution, and characterization of C. difficile strains isolated from pregnant women without diarrhea in China. As part of this study, 3.7% (37 out of 1009) of samples acquired from pregnant females tested positive for C. difficile. Of these positive samples, 27.0% (10) were toxigenic isolates containing both toxin A and toxin B genes (A+B+), 13.5% (5) of the variant strains contained the toxin B gene (A−B+) only, while the rest were non-toxigenic isolates (59.5%, 22 isolates). Among the non-pregnant women without diarrhea tested, 1.4% (9 of 651) contained toxigenic isolates (all of which were A+B+). Sixteen different sequence types (STs) were isolated during the course of this study. ST-37 (ribotype 017) and ST-54 (ribotype 012) were the most frequent toxigenic types observed in pregnant women. All strains showed susceptibility to the antibiotics metronidazole and vancomycin. The resistance rates of toxigenic C. difficile strains isolated from pregnant females to clindamycin, erythromycin, moxifloxacin, levofloxacin, and rifampicin were 20%, 46.7%, 13.6%, 46.7% and 13.3%, respectively. There was no significant difference between resistance rates of toxigenic and non-toxigenic strains with respect to their susceptibility to these antibiotics. However, when compared with the same data from non-pregnant women, toxigenic strains from pregnant women showed lower resistance rates to clindamycin ( P < 0.05). Highlights: This study was the first survey of Clostridium difficile carriage rates in pregnant women. Significant diversity of sequence types in C. difficile isolated was observed. There was no difference in drug resistance between strains with toxigenicity or not.